The roles of agroclimatic similarity and returns on scale in the demand for mechanization: Insights from northern Nigeria - Takeshima, Hiroyuki (International Food Policy Research Institute, 2017)
Using farm household data from northern Nigeria as well as various spatial agroclimatic data, this study shows that the adoption of key mechanical technologies in Nigerian agriculture (animal traction, tractors, or both) has been high in areas that are more agroclimatically similar to the locations of agricultural research and development (R&D) stations, and this effect is heterogeneous, being particularly strong among relatively larger farms. Furthermore, such effects are likely to have been driven by the rise in returns on scale in the underlying production function caused by the adoption of these mechanical technologies. Agricultural mechanization, represented here as the switch from manual labor to animal traction and tractors, has been not only raising the average return on scale but also potentially magnifying the effects of productivity-enhancing public-sector R&D on spatial variations in agricultural productivity in countries like Nigeria.